Genetics : analysis of genes and genomes - Hartl, Daniel L., 1943-; Jones, Elizabeth Winifred, 1939-2008 (Sudbury (Mass.) : Jones and Bartlett, 2009)
Written by two renowned authorities, Genetics: Analysis of Genes and Genomes, Seventh Edition provides the most current, clear, comprehensive and balanced introduction to genetics and genomics at the college level. Expanding upon the key elements that have made the text a success, the authors have added important new material to virtually every chapter, including sections on High-throughput genotyping, massively parallel sequencing, comparative genomics, genomic islands, copy number polymorphisms, characteristics of Quantitative Trait Loci for disease risk factors, and much more. They continue to treat transmission genetics, molecular genetics, and evolutionary genetics as fully integrated subjects and provide students with an unprecedented understanding of the basic process of gene transmission, mutation, expression and regulation. Integrated critical thinking exercises and problem sets allow for a mastery of key genetic concepts, while the end-of-chapter Guide to Problem-Solving sections demonstrate the concepts needed to efficiently solve problems and understand the reasoning behind the correct answer.
Includes bibliographical references and index.
Keywords: Genetica; Genetics